Evaluación, análisis y optimización de los sistemas de entrepiso Plycem para cargas gravitacionales - Quesada-Solano, Jose Luis (Instituto Tecnológico de Costa Rica, 2011)
Plycem, a company specialized in fiber cement products, offers mezzanine floor in which 22 mm plates over C cold rolled contours are utilized. Some clients who have used this system have been affected by service charges. Therefore, it is necessary to develop improvements to enhance its quality. In order to accomplish these quality improvements, it is necessary to perform evaluation, analysis and optimization tasks towards the main usage conditions flaws within these structures. When testing Plycem mezzanine floor systems, customers and professionals in the construction field were interviewed and similar case studies were considered. Based on this analysis, the vibration and the fissuring of the mezzanine floor are considered to be the main flaws. Using design tables and studying the gathered information during the process allowed the analysis of these floor systems. During this stage qualitative- quantitative results about the main flaws were obtained. This project is completed with the proposal for optimization alternatives. In this aspect, tests to measure the placement of ceramic over geotextile were performed and options to decrease vibration were developed. Results from this study suggest that the building process for Plycem mezzanine floor systems requires appropriate technical support, inspection and the use of solutions to prevent flaws according to the proposals provided.
Proyecto de graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2011.
Keywords: Evaluación del desempeño; Láminas de fibrocemento; Vibración; Cerámica; Reforzamiento; Entrepiso